Literature review of conjunctivitis, conjunctival swab and chloroquine effect in the eyes: a current updates on COVID-19 and ophthalmology - Indra Tri Mahayana; Natalia Christina Angsana; Alya Kamila; Nisrina Nur Fatiha; Devin Zen Sunjaya; Winanto Andajana; Suhardjo Suhardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
This overview briefly describes current literature findings in ophthalmology related to coronavirus disease 2019 (COVID-19) that become a worldwide pandemic. It included the current updates related to conjunctivitis that believed as the early sign of COVID-19, the effectiveness of conjunctival swab in detecting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) compared to naso- or oropharyngeal swab and the long-term side effect of chloroquine use to the eyes. The analysis from four current published literatures revealed, overall sensitivity of conjunctivitis was 2.42% (CI 95%: 0.79-5.55) and conjunctival swab was 2.90% (CI 95%: 1.07-6.20). There were no current COVID-19-related literatures discussing the side effect of chloroquine to the eyes, however, previous literatures revealed there were potential long-term harmful effects of chloroquine treatment to the eyes.